Analisis keterbacaan teks narasi pada buku siswa kelas IV SD tema 4 “berbagai pekerjaan” kurikulum 2013 menggunakan grafik fry - Nurhidayah, Firsta Novia; Winarni, Retno; Surya, Anesa (Didaktika Dwija Indria, 2021)
The purpose of this research is to analyze readability of the narrative text using fry graph. The scope of this research is the narrative text contained in the student book of fourth grade elementary school theme 4 “berbagai pekerjaan” in the curriculum 2013, which consists of 13 narrative texts. The research method of this study is descriptive analysis, the data that has been collected and then analyzed for readability using the fry graph. Based on the legibility formula introduced by Edward Fry, the main factors affecting the level of readability are two things, “the short length of the sentence” and “the syllables that make up the words in each text”. After calculating with the fry graph formula, it was found that the narrative text contained in the fourth grade elementary school theme 4 “berbagai pekerjaan” in the curriculum 2013 is more suitable for grades 1,2 and 3.